Adsorptive Desulfurization of Organic Sulfur from Model Fuels by Active Carbon Supported Mn (II): Equilibrium, Kinetics, and Thermodynamics - Jianhong Wang; Qi Zhang; Hao Yang; Congzhen Qiao (International Journal of Chemical Engineering)
Mn (II)/AC adsorbents were prepared by ultrasonic impregnation. The 2 wt. % Mn/AC showed best adsorptive performance, and the optimal adsorption temperature was 313 K. Benzene, methylbenzene, and naphthalene were used to explore the adsorptive selectivity of Mn/AC, indicating that Mn could enhance the adsorptive capacity but could not improve the adsorptive selectivity. The adsorptive mechanism was mostly like to be π-complex. Adsorptive isotherms and kinetics were investigated, and the parameters were calculated. The R2, RMSE, and AICc were used to assess the optimal model. The results showed that Temkin adsorptive isotherm was more suitable to describe the isothermal data; the MPnO kinetics model was more superior to other kinetic models. The order of reaction was between 1 and 2. The outcome of adsorptive thermodynamics indicated that removal of DBT onto Mn/AC was a spontaneous and exothermic process.